Role of carbonate electrolytes on interaction of quinolone drug with anionic surfactant at various temperatures: A conductometric study. (16th August 2020) - Mahbub, Shamim; Islam, Mohayminul; Masum, Abuzayed; Akter, Parul; Hoque, Md. Anamul; Kumar, Dileep; Khan, Farah; Rub, Malik Abdul; Alfaifi, Sulaiman Y.M.; Asiri, Abdullah M.
Abstract: The role of different carbonate salts on the interaction of anionic surfactant sodium dodecyl sulfate (SDS) with employed quinolone antibiotic drug (ciprofloxacin hydrochloride [CFH]) was explosively inspected through measuring specific conductivity ( κ ) of the investigated system. The drug, CFH, is an excellent antibiotic for the treatment of different bacterial infections like skin, urinary tract, and respiratory infections. The estimated critical micelle concentrations ( cmc ) of SDS were observed to be dwindled in the attendance of electrolytes and cmc reduction continues with the escalation of the electrolyte's concentration. The magnitudes of cmc for the SDS + CFH mixture were reduced with the elevation of temperature in K2 CO3 and CaCO3 medium while increased with the rise of the temperature in the Na2 CO3 medium. The magnitudes of counterion binding to micelles ( β ) were increased with the increase of the concentration of Na2 CO3 and K2 CO3 up to definite value and then reduced with the increase of successive rise of concentration of both salts at all temperatures while decreased monotonically with the rise of electrolyte concentration in CaCO3 medium. The values of standard free energy ( ∆ G m o ) were achieved to be negative in each case suggesting spontaneous self‐assembly formation. The standard entropy change ( ∆ S m o ) along with enthalpy change ( ∆ H m o ) was also assessed and discussed elaborately. Abstract : Herein, the role of different carbonate salts on the interaction of sodium dodecyl sulfate (SDS) with employed quinolone antibiotic drug was explosively inspected. The estimated critical micelle concentrations ( cmc ) of SDS were observed to dwindle in the attendance of electrolytes. The values of standard free energy ( ∆ G m o ) were achieved to be negative in each case suggesting spontaneous self‐assembly. The standard entropy change ( ∆ S m o ) along with enthalpy change ( ∆ H m o ) were also assessed and discussed elaborately.